Teachers' Beliefs and Practices on Teaching-Reading: A Case Study at SMP Muhammadiyah 10 Surakarta - Sajad, S.W, Prof.Dr.Endang Fauziati, M.Hum, Mauly Halwat Hikmat, Ph. D (2017)
This research was a case study of English teachers' beliefs and practices on teaching- reading at SMP Muhammadiyah 10 Surakarta. The objectives of this study were: (1) to investigate the teachers' beliefs in teaching-reading. These involve objectives learning, classroom technique, teachers and students roles in teaching reading, the role of authentic material at SMP Muhammadiyah 10 Surakarta, (2) to investigate how the teachers' beliefs are reflected in the classroom practices, (3) to investigate whether there are some discrepancies between teachers' beliefs and their pratices in teaching, (4) to investigate factors contribute to these discrepancies, (5) to investigate factors contribute with shape the teachers' beliefs on teaching-reading. The type of the research was qualitative with case study approach. It was an investigation of a single case or collective case to capture the complexity of objects of the study. The object of the study was teachers' beliefs of English teaching at SMP Muhammadiyah 10 Surakarta. The subjects of the study were two English teachers consisting of two female teachers. The data sources used in this study were: classroom observation, open ended questionnaire, transcript of interview and document. The techniques f o r collecting data used were open-ended questionnaire, semi-structured interview, classroom observation and document analysis taken from the informants. The data validity used was data triangulation to gain accountable information through a variety of sources. Then, the researcher used Miles and Hubberman's Model (1993) to analyze the data. The finding of this study showed that first, most of the teachers' beliefs on teaching-reading were consistent with their practices namely beliefs about learning objective, teacher' role, student' role, the role of authentic material and component of reading skill although the researcher still found one discrepancy namely teachers' beliefs about classroom technique. The factors contributing to shape teachers' beliefs were (1) experience as language learners (2) experience from teaching, (3) and training.